“The Solar System and Beyond” How Teachers Teaching This Unit? - Esra Yılmaz; Canan Laçin Şimşek (Sakarya University Journal of Education)
The subjects of the science class are composed of the life itself. These subjects include the subjects that can be experienced with simple observations such as motion and matter and the subject that cannot be observed directly such as the atom, cell and space. Therefore, it is necessary that the teachers should make preparations for the subjects in order for the students to comprehend these concepts accurately. “The Solar System and Beyond” unit that is lectured at the 7th grade is one of the subjects that must be supported with the images and materials. Thus, this study aims to determine the methods used in this unit and the problems that the teachers encounter. This is a phenomenological study. The data is obtained by interviewing 49 teachers working in Sakarya province with the easily accessible sample method. The data obtained is examined with the concept analysis and presented in an analytic method. As a result, the teachers expressed that the “Solar System and Beyond” unit lectured at the 7th grade is necessary for the students and they implement visual material, video, animation and documents as well as the smart board applications to support the unit. The majority of the teachers expressed that the students are interested in the astronomy, but it is a disadvantage that this unit is the last unit.